Impact of zinc substitution on the structural and magnetic properties of chemically derived nanosized manganese zinc mixed ferrites - Gopalan, E. Veena; Al-Omari, I. A.; Malini, K. A.; Joy, Pattayil Alias; Kumar, D. Sakthi; Yoshida, Yasuhiko; Anantharaman, Maliemadom R. (Journal of Magnetism and Magnetic Materials, 2009)
Mn(1-x)Zn(x)Fe(2)O(4) nanoparticles (x = 0-1) were synthesized by wet chemical co-precipitation techniques. X-ray diffraction, transmission electron microscopy and high-resolution transmission electron microscopy were effectively utilized to investigate the different structural parameters. The elemental analysis was conducted using energy-dispersive spectrum and inductively coupled plasma analysis. The magnetic properties such as magnetization and coercivity were measured using vibrating sample magnetometer. The observed magnetization values of the nanoparticles were found to be lower compared to the bulk counterpart. The magnetization showed a gradual decrease with zinc substitution except for a small increase from x = 0.2 to 0.3. The Curie temperature was found to be enhanced in the case of ferrites in the nanoregime. The variation in lattice constant, reduced magnetization values, variation of magnetization with zinc substitution, the presence of a net magnetic moment for the zinc ferrite and the enhancement in Curie temperature in Mn(1-x)Zn(x)Fe(2)O(4) all provide evidence to the existence of a metastable cation distribution together with possible surface effects at the nanoregime. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Manganese zinc ferrite